The Effect Of Profitability, Liquidity, And Company Growth On Asset Structure - Sabrina Rizky Amalia; Nabila Rahmadayanti; Sindy Larasasti; Putri Utami Permata Sari; Meigia Nidya Sari (CV. AFDIFAL MAJU BERKAH, 2025)
This study is intended to explain the impact of profitability, liquidity, and firm growth on asset structure. The sample in this study includes 138 data selected from 48 industrial companies in IDX for 4 years using purposive sampling system. The data analysis technique used for this research includes panel data regression analysis processed with the help of Eviews 12 application. The results show that profitability and firm growth have a negative effect on asset structure, while liquidity does not have any effect on asset structure.